RIPLET, and not TRIM25, is required for endogenous RIG‐I‐dependent antiviral responses. Issue 9 (19th August 2019) - Hayman, Thomas J; Hsu, Alan C; Kolesnik, Tatiana B; Dagley, Laura F; Willemsen, Joschka; Tate, Michelle D; Baker, Paul J; Kershaw, Nadia J; Kedzierski, Lukasz; Webb, Andrew I; Wark, Peter A; Kedzierska, Katherine; et al.
Abstract: The innate immune system is our first line of defense against viral pathogens. Host cell pattern recognition receptors sense viral components and initiate immune signaling cascades that result in the production of an array of cytokines to combat infection. Retinoic acid–inducible gene‐I (RIG‐I) is a pattern recognition receptor that recognizes viral RNA and, when activated, results in the production of type I and III interferons (IFNs) and the upregulation of IFN‐stimulated genes. Ubiquitination of RIG‐I by the E3 ligases tripartite motif‐containing 25 (TRIM25) and Riplet is thought to be requisite for RIG‐I activation; however, recent studies have questioned the relative importance of these two enzymes for RIG‐I signaling. In this study, we show that deletion of Trim25 does not affect the IFN response to either influenza A virus (IAV), influenza B virus, Sendai virus or several RIG‐I agonists. This is in contrast to deletion of either Rig‐i or Riplet, which completely abrogated RIG‐I‐dependent IFN responses. This was consistent in both mouse and human cell lines, as well as in normal human bronchial cells. With most of the current TRIM25 literature based on exogenous expression, these findings provide critical evidence that Riplet, and not TRIM25, is required endogenously for the ubiquitination of RIG‐I. Despite this, loss of TRIM25 results in greater susceptibility to IAV infection in vivo, suggesting that it may have an alternative role in host antiviral defense. This study refines our understanding of RIG‐I signaling in viral infections and will inform future studies in the field. Abstract : Ubiquitination of RIG‐I by the E3 ligases TRIM25 and Riplet is thought to be requisite for RIG‐I activation; however, recent studies have questioned the relative importance of these two enzymes for RIG‐I signaling. In this study, we show that deletion of Trim25 does not affect the IFN response to either influenza A virus, influenza B virus, Sendai virus or several RIG‐I agonists. This is in contrast to deletion of either Rig‐i or Riplet, which completely abrogated RIG‐I‐IFN responses.